Patterns of Regression in Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Patterns and features of regression in a case series of 53 girls and women with Rett syndrome were studied at the Institute of Child Health and Great Ormond Street Children's Hospital, London, UK.